Hyperosmolar stress upregulates HLA-DR expression in human conjunctival epithelium in dry eye patients and in vitro models - Versura, Piera; Profazio, Vincenzo; Schiavi, Costantino; Campos, Emilio C (Investigative ophthalmology & visual science, 2011)
To investigate the immune response of human conjunctival epithelium to hyperosmolar stress. Tear osmolarity was measured in 15 normal subjects and 25 dry eye (DE) patients; conjunctival imprint cytology samples were obtained at the nasal bulbar area. Subconfluent primary human conjunctival epithelial cells (pHCECs) and human conjunctival organ cultures (hCOCs), both cultured in iso-osmolar medium (305 mOsm/L), were exposed for 24 hours to media with progressively higher osmolarity, with or without the ion channel inhibitor ruthenium red (RuR). Human leukocyte antigen (HLA)-DR expression was evaluated by immunocytochemistry, on imprints from subjects, on primary human conjunctival epithelial cells, on formalin fixed-paraffin embedded hCOCs, and by RT-PCR. Statistical evaluation was performed by applying the unpaired Student's t test, as well as Spearman's rho and Pearson's r correlation coefficients (significance P < 0.05). HLA-DR expression increased in DE subjects with respect to control (% mean ± SD, respectively, 46.16 ± 7.2 vs. 7.48 ± 1.14, P < 0.0001) and exhibited significantly high correlations with tear osmolarity values (r = 0.614; P < 0.0001). In vitro experiments showed a progressive increase in HLA-DR expression as the osmolarity of the medium was increased from 6.75 ± 1.16 (% mean ± SD) in iso-osmolar-cultured cells to 9.96 ± 1.37 and 12.94 ± 4.04 in cells cultured in, respectively, 350 and 400 mOsm/L (P < 0.05). A stepwise progressive increase was also found in hCOCs. Results were confirmed by RT-PCR. Ruthenium red significantly reduced HLA-DR expression in hyperosmolar-cultured cells. Data from complementary techniques demonstrate that extracellular hyperosmolarity induces HLA-DR overexpression in human conjunctival epithelial cells in both DE patients and in vitro cell culture models.